2016
DOI: 10.1021/jacs.6b04548
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-Responsive and “Clickable” Poly(ethylene glycol) via Copolymerization of 2-(Methylthio)ethyl Glycidyl Ether

Abstract: Poly(ethylene glycol) (PEG) is a widely used biocompatible polymer. We describe a novel epoxide monomer with methyl-thioether moiety, 2-(methylthio)ethyl glycidyl ether (MTEGE), which enables the synthesis of well-defined thioether-functional poly(ethylene glycol). Random and block mPEG-b-PMTEGE copolymers (Mw/Mn = 1.05-1.17) were obtained via anionic ring opening polymerization (AROP) with molecular weights ranging from 5 600 to 12 000 g·mol(-1). The statistical copolymerization of MTEGE with ethylene oxide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 64 publications
(190 reference statements)
2
89
1
1
Order By: Relevance
“…Subsequently, the in situ oxidation of PPS from hydrophobic thioether to sulfoxide and finally hydrophilic sulfone results in efficient degradation of the Au-LAHP-vDOX and release of cargo drugs. [16] In this manner, drug release is synchronously confined when radiation therapy is applied, which may largely mitigate possible development of resistance to monotherapy and in turn potentiate the maximal synergism in chemoradiation therapy. [17] Meanwhile, this approach may also benefit from the radiation dose enhancement effect by the high atomic number (Z) Au NPs and the ROS mediated mechanisms for improving treatment outcomes.…”
mentioning
confidence: 99%
“…Subsequently, the in situ oxidation of PPS from hydrophobic thioether to sulfoxide and finally hydrophilic sulfone results in efficient degradation of the Au-LAHP-vDOX and release of cargo drugs. [16] In this manner, drug release is synchronously confined when radiation therapy is applied, which may largely mitigate possible development of resistance to monotherapy and in turn potentiate the maximal synergism in chemoradiation therapy. [17] Meanwhile, this approach may also benefit from the radiation dose enhancement effect by the high atomic number (Z) Au NPs and the ROS mediated mechanisms for improving treatment outcomes.…”
mentioning
confidence: 99%
“…To investigate the degradation kinetics of both PEG‐ketal‐diols and PEG‐ketal‐DMA macromonomers, we measured the in situ 1 H NMR kinetics of the degradation of macromonomers dissolved in deuterated phosphate buffer solutions buffered to different pH values (degradation scheme see Scheme S1 in the Supporting Information). In situ 1 H NMR measurements have been extensively used to monitor polymerization reactions online . It is also possible to use this technique to analyze the cleavage of ketal macromonomers by monitoring the changes of typical NMR signals in situ during the hydrolysis reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of thioethers, in contrast to regular ethers the nature of sulfur provides the possibility of functionalization, while representing a more stable option than disulfides and thiol groups, which is essential for biomedical applications since a precise targeting requires a structure which remains unchanged until it is required . During the last years the incorporation of thioethers for stimuli‐responsive materials has been a deal of research effort, for instance, Tirelli and co‐workers reported the potential of polythioethers as redox‐responsive nanocarriers for inflammation targeting, remarking that hydrophobic thioethers could be oxidized in the milieu of inflamed tissue, changing the hydrophobic/hydrophilic balance with disassembly of the nanostructure, and Long and co‐workers, who studied sulfone‐functional poly(methyl methacrylate) (PMMA) derivatives, found them to be nonviral nucleic acid delivery agents and confirmed their high potential for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%